Methods of Calculating the Marginal Cost of Incarceration: A Scoping Review - Wilson, Stuart John (Criminal justice policy review, 2022)
Criminal justice reforms and corrections cost forecasts require appropriate estimates of the marginal costs of incarceration to adequately assess cost savings and projections. Average costs are simple to calculate while marginal cost calculations require much more detailed data and advanced methods. We undertook a scoping review to identify, report, and summarize the existing academic and gray literature covering the different estimation methods of calculating the marginal costs of incarceration, following the Arksey and O’Malley framework. Eighteen publications met criteria for inclusion in this review, with only one from the peer-reviewed literature. The three main approaches in the literature and their use are reviewed and illustrated. We conclude that there is a lack of, and need for, peer-reviewed literature on methods for calculating the marginal cost of incarceration, and marginal cost estimates of incarceration, to assist program evaluation, policy, and cost forecasting in the field of corrections.